PI3KC3-dependent autophagosomes formation pathway is of crucial importance to anti-DHAV activity of Chrysanthemum indicum polysaccharide. (15th March 2019) - Ming, Ke; Yuan, Wenjuan; Chen, Yun; Du, Hongxu; He, Miao; Hu, Yuanliang; Wang, Deyun; Wu, Yi; Liu, Jiaguo
Highlights: The role of autophagy in DHAV replication was demonstrated for the first time. CIPS inhibited DHAV replication by impairing the formation of autophagosomes. CIPS inhibit autophagosomes formation by downregulating the activity of PI3KC3. Abstract: We previously reported that Chrysanthemum indicum polysaccharide (CIPS) effectively inhibited the replication of duck hepatitis A virus (DHAV). However, the inhibition mechanisms are still unclear. Autophagy plays important role in virus genomic replication. Therefore, in present study, the effect of autophagy on DHAV genome replication as well as the influence of CIPS on autophagy were studied. qPCR, western blot, and ELISA methods were applied to observe the autophagy and analyze the inhibition mechanisms of CIPS on DHAV. Results showed that DHAV infection increased the expression level of LC3-II and interdicted the degradation of p62. Treating with rapamycin benefited DHAV gene expression level. What's more, DHAV infection and rapamycin treatment also promoted the expression of PI3KC3 and increased the concentration of PI3P. However, CIPS treatment significantly downregulated the expressions of LC3-II and PI3KC3 induced by DHAV and rapamycin, and consequently inhibited autophagosomes formation. As a result, DHAV replication was inhibited.